Measured and modeled variation in pollutant concentration near roadways - Gordon, Mark; Staebler, Ralf M.; Liggio, John; Li, Shao-Meng; Wentzell, Jeremy; Lu, Gang; Lee, Patrick; Brook, Jeffrey R. (ATMOSPHERIC ENVIRONMENT, 2012)
This paper presents a study of the evolution of particles and gases downwind of a highway, with a focus on the diurnal variation of pollutant gradients and its controlling variables. A mobile laboratory was used to measure the concentration gradients of ultra-fine particles (UFP), black carbon (BC), CO2, NO, and NO2 at varying distances up to 850 m from a major highway. The horizontal distributions of pollutants show a strong diurnal pattern. Results suggest that the horizontal gradients are predominantly influenced by traffic levels, friction velocity, and atmospheric stability. The results were compared to a dispersion model, which showed good agreement with the measurements and was able to qualitatively capture the observed diurnal cycles. Emission rates [g km(-1)] calculated from the model fits are within 10% of the Mobile 6.2C inventory for CO2 and demonstrate good agreement for NOx, but are higher than the inventory by a factor between 2.0 and 5.9 for black carbon. Hourly NOx emission rates correlate with the fraction of heavy-duty vehicles in the total fleet and agree with inventory values based on maximum vehicle emission rates. Crown Copyright (C) 2012 Published by Elsevier Ltd. All rights reserved.